Coagulation function of stored whole blood is preserved for 14 days in austere conditions: A ROTEM feasibility study during a Norwegian antipiracy mission and comparison to equal ratio reconstituted blood. (June 2015) - Strandenes, Geir; Austlid, Ivar; Apelseth, Torunn O.; Hervig, Tor A.; Sommerfelt-Pettersen, Jan; Herzig, Maryanne C.; Cap, Andrew P.; Pidcoke, Heather F.; Kristoffersen, Einar K.
Abstract : BACKGROUND: Formulation of a medical preparedness plan for treating severely bleeding casualties during naval deployment is a significant challenge because of territory covered during most missions. The aim of this study was to evaluate the concept of "walking blood bank" as a supportable plan for supplying safe blood and blood products. METHODS: In 2013, the Royal Norwegian Navy conducted antipiracy operations from a frigate, beginning in the Gulf of Aden and ending in the Indian Ocean. Crews were on 24-hour emergency alert in preparation for an enemy assault on the frigate. Under an approved command protocol, a "walking blood bank, " using crew blood donations, was established for use on board and on missions conducted in rigid-hulled inflatable boats, during which freeze-dried plasma and leukoreduced, group O low anti-A/anti-B titer, cold-stored whole blood were stored in Golden Hour Boxes. Data demonstrating the ability to collect, store, and provide whole blood were collected to establish feasibility of implementing a whole blood–focused remote damage-control resuscitation program aboard a naval vessel. In addition, ROTEM data were collected to demonstrate feasibility of performing this analysis on a large naval vessel and to also measure hemostatic efficacy of cold-stored leukoreduced whole blood (CWB) stored during a period of 14 days. ROTEM data on CWB was compared with reconstituted whole blood. RESULTS: Drills simulating massive transfusion activation were conducted, in which 2 U of warm fresh whole blood with platelet sparing leukoreduction were produced in 40 minutes, followed by collection of two additional units at 15-minute increments. The ROTEM machine performed well during ship-rolling, as shown by the overlapping calculated and measured mechanical piston movements measured by the ROTEM device. Error messages were recorded in 4 (1.5%) of 267 tests. CWB yielded reproducible ROTEM results demonstrating preserved fibrinogen function and platelet function for at least 3.5 weeks and 2 weeks, respectively. The frequency of ROTEM tests were as follows: EXTEM (n = 88), INTEM (n = 85), FIBTEM (n = 82), and APTEM (n = 12). CWB results were grouped. Compared with Days 0 to 2, EXTEM maximum clot firmness was significantly reduced, beginning on Days 10 to 14; however, results through that date remained within reference ranges and were comparable with the EXTEM maximum clot firmness for the reconstituted whole blood samples containing Day 5 room temperature–stored platelets. CONCLUSION: A "walking blood bank" can provide a balanced transfusion product to support damage-control resuscitation/remote damage-control resuscitation aboard a frigate in the absence of conventional blood bank products. ROTEM analysis is feasible to monitor damage-control resuscitation and blood product quality. ROTEM analysis was possible in challenging operational conditions. LEVEL OF EVIDENCE: Therapeutic study, level V.